Dydaktyka literatury w perspektywie badań komunikacji literackiej = Didactics of Literature in the Perspective of Literary Communication Researches - Polakowski, Jan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article shows the possibi1ity to enrich the field of methodical didactics of Literature by means of takling advantage of experiences in literary communication. The starting point of the argumentation is the analysis of different principles in the formulation of practicable statements in the field of that didactic theory, which engages in questions of understandinga piece of literary work by young people
Keywords: dydaktyka literatury; badania; komunikacja literacka